Rationale and design of a statewide telestroke registry: Lone Star Stroke Consortium Telestroke Registry (LeSteR). Issue 9 (4th September 2019) - Astudillo, Cesar; Ankrom, Christy; Trevino, Alyssa; Malazarte, Rene M; Bambhroliya, Arvind B; Savitz, Sean; Topel, Christopher H; Milling, Truman J; Wu, Tzu-Ching
Abstract : Introduction: The Lone Star Stroke Consortium Telestroke Registry (LeSteR) currently consisting of 3 academic hub centres and 27 partner spokes is a statewide initiative organised by leading academic health centres in the State of Texas to understand practice patterns of acute stroke management via telestroke (TS) in Texas, a state with one of the largest rural populations in the USA. Methods and analysis: All patients who had presumed stroke for whom a TS consultation has been obtained in the network are entered into a web-based, Health Insurance Portability and Accountability Act-compliant database from September 2013 to present. Spokes were enrolled into LeSteR in a staggered approach in two data collection phases: a retrospective phase and a prospective phase. Basic clinical, demographic data and relevant time metrics are collected in the retrospective phase. Starting 1 September 2015, additional outcome data including 90-day modified Rankin score, readmission and 90-day disposition are obtained by a standard phone interview. From the registry initiation to 31 December 2017, there are 8089 patients who had suspected stroke in the registry. Over 60% of patients enrolled after 1 September 2015 have reported outcome data. Enrolment is still active for this registry. Ethics and dissemination: LeSteR is a statewide TS registry organised by academic health centres that will provide significant insight regarding the impact of TS in the State of Texas. Findings from LeSteR will provide data that can be analysed to improve the allocation of healthcare resources using TS to treat stroke in a state with one of the largest rural populations.